Integrative genomic analysis identifies the core transcriptional hallmarks of human hepatocellular carcinoma Running title: Transcriptional hallmarks of liver cancer - Allain, Coralie (Cancer Res, 2016)
Integrative genomics helped characterize molecular heterogeneity in HCC, leading to targeted drug candidates for specific HCC subtypes. However, no consensus was achieved for genes and pathways commonly altered in HCC. Here we performed a meta-analysis of 15 independent datasets (n=784 human HCC) and identified a comprehensive signature consisting of 935 genes commonly deregulated in HCC as compared to the surrounding non-tumor tissue. In the HCC signature, up-regulated genes were linked to early genomic alterations in hepatocarcinogenesis, particularly gains of 1q and 8q. The HCC signature covered well-established cancer hallmarks, such as proliferation, metabolic reprogramming, and microenvironment remodeling, together with specific hallmarks associated with protein turnover and epigenetics. Subsequently, the HCC signature enabled us to assess the efficacy of signature-relevant drug candidates, including histone deacetylase inhibitors that specifically reduced the viability of six human HCC cell lines. Overall, this integrative genomics approach identified cancer hallmarks recurrently altered in human HCC that may be targeted by specific drugs. Combined therapies targeting common and subtype-specific cancer networks may represent a relevant therapeutic strategy in liver cancer.